The social justice dilemma of liability allocation in medical damage: a qualitative analysis based on case judgments - Yilin Hu (Frontiers in Public Health, 2026)
Currently, medical liability regimes in numerous jurisdictions face common dilemmas and challenges linked to social justice. Issues such as excessive medical litigation, the pervasive practice of defensive medicine, and escalating doctor–patient conflicts have significantly negatively affected the operations of global healthcare systems, progressively eroding the foundation of social justice. This has prompted legislative bodies to reevaluate and reform existing medical policies and the structural framework of medical liability systems. The definition and allocation of medical liability require reexamination to prevent liability rules from disproportionately favoring either patients or physicians, thereby advancing the social goals of establishing a “doctor–patient community” and realizing “doctor–patient justice.” The factual causation linkage between medical negligence and patient harm constitutes the core element and “control valve” for the establishment of medical liability, and this area requires continuous advancement in both theoretical research and practical application. This study adopts qualitative case analysis and interpretive theoretical methods as the primary approaches to investigate value conflicts, institutional deficiencies, and context-dependent practical significance embedded in typical medical liability cases. Comparative legal methodology is further employed to explore the root causes, impacts, reform paths and theoretical innovations underlying the alienation of medical liability. This article argues that within the framework of social justice, the “gap-filling principle” derived from tort law theory is insufficient to resolve entrenched doctor–patient conflicts, and the theoretical orientation needs to shift from an exclusive focus on damage compensation to the integration of multiple normative objectives. Proportional causation theory, constructed on the basis of the minimum likelihood probability principle, and the corresponding proportional liability provide groundbreaking insights for resolving the dilemma of determining factual causation standards in medical liability cases. This theory can be integrated with proportional liability under the causative potency doctrine, forming a structurally layered synergistic mechanism to reconstruct the proportional compensation liability for medical damage cases at the level of legal causation. The core solution to the social justice dilemma lies in establishing a dynamic and systematic medical liability regime that (i) clarifies the hierarchical relationship between patient damage remedies, medical professional freedom and social costs; (ii) strikes a balance among patient safety, medical innovation and liability accountability; (iii) realizes risk socialization through mandatory medical liability insurance; and (iv) explores diversified social risk-sharing and healthcare security mechanisms. Ultimately, this approach facilitates the coexistence and mutual promotion of interests among medical institutions, patients, the medical industry and the public.